2021
DOI: 10.52082/jssm.2022.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Position on Peak Eccentric Force during The Nordic Hamstring Exercise

Abstract: Peak eccentric force during the Nordic hamstring exercise (NHE) is recognized as a predictive factor for hamstring strain injury (HSI). During the NHE, the knee flexor muscles are eccentrically contracting to resist the knee joint extension. Therefore, it is thought that the action of the gastrocnemius muscle, and thus the ankle position, influences peak eccentric force during the NHE. However, the effect of ankle position on peak eccentric force during the NHE remains unclear. Therefore, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, Ahmad et al (2021) showed that hamstrings stretching in combination with suboccipital manual techniques is more effective in increasing hamstring muscles ROM than local stretching alone. In terms of force generation, it has been shown that ankle position and training of the foot muscles influence hamstrings strength (Sulowska et al 2019;Nishida et al 2022). These findings suggest strain transfer along the superficial back line via fascial pathways in the lower extremity and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ahmad et al (2021) showed that hamstrings stretching in combination with suboccipital manual techniques is more effective in increasing hamstring muscles ROM than local stretching alone. In terms of force generation, it has been shown that ankle position and training of the foot muscles influence hamstrings strength (Sulowska et al 2019;Nishida et al 2022). These findings suggest strain transfer along the superficial back line via fascial pathways in the lower extremity and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Fig 1 shows the setting of the NHE and RHC. As described previously [6,7], each participant was placed in a kneeling position on a custom-made NHE device, and each ankle was secured over the lateral ankle by an ankle brace attached to a load cell. The force against the ankle brace in the vertical direction was measured by the load cell connected to a PowerLab16/35 (AD Instruments, Bella Vista, Australia), synchronously transferred the force data to a personal computer (VersaPro; NEC, Tokyo, Japan) at 1000 Hz [6].…”
Section: Nordic Hamstring Exercise and Razor Hamstring Curl Strength ...mentioning
confidence: 99%
“…Nordic hamstring exercise (NHE) is a training in which the patient gradually leans forward from a kneeling posture with the ankle fixed and the knee joint flexed 90˚ [6,7]. NHE is beneficial for preventing HSI [8] because hamstring ECC muscle strength [9][10][11], and fascicle length [8,9] increase.…”
Section: Introductionmentioning
confidence: 99%